O programa nacional para produção e uso do biodiesel na realidade da agricultura familiar de Rio Verde-GO - Resende, Renata Maria de Miranda Rios (2015)
The National Program for the Production and Use of Biodiesel (PNPB) was created in Brazil to meet economic, environmental and social issues. Under the social focus, is the inclusion of family farmers in the biodiesel chain, which receives incentives to produce and supply raw material for biofuel production, so that this farmer can stay on the field with dignity. In this respect, the family farmer of Rio Verde - GO has been benefited by this program? This work was general objective to diagnose the inclusion of family farming in Rio Verde PNPB. As specific objectives, sought to identify the effectiveness of contracts and their influence on entry and stay of that farmer in the program; know the assessment that the farmer makes PNPB and its perception as to any possible improvement of life with participation in the program. The study gathered the Federation of Agricultural Workers of the State of Goiás (FETAEG), the Union of Rural Workers of Rio Verde (STRRV), cooperatives of farmers A and B operating in the municipality, four representatives of the five companies that also act in the city in the biodiesel industry and have the Social Fuel Seal (SCS) and 43 family farmers of Rio Verde entered into PNPB, defined from a non-probability sample intentional. The results showed that family farming in Rio Verde is set in a different context, in which among other factors, have soybean as product already traditional; that the contracts governance structure has not yet been able to curb opportunistic behavior of the parties, and the farmer is in a more fragile situation; that the majority of respondents farmers realized an improvement of life in program function, and that most of farmers do a positive assessment of PNPB, although there are many complaints about the same.